2012
DOI: 10.1071/ch12010
|View full text |Cite
|
Sign up to set email alerts
|

Oxygenated Terpenoids from the Australian Sponges Coscinoderma matthewsi and Dysidea sp., and the Nudibranch Chromodoris albopunctata

Abstract: The isolation and structure elucidation of seven new oxygenated terpenoids and eight known terpene metabolites from marine invertebrates collected at the Inner Gneerings Reef, South East Queensland, is discussed. Investigation of the sponge Coscinoderma matthewsi yielded an epoxylactone derivative (1) of the known furanoterpene tetradehydrofurospongin-1 (2). A chemical investigation of the dissected nudibranch Chromodoris albopunctata provided the new oxygenated diterpenes 12α-acetoxyspongian-16-one (10), 20-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(46 citation statements)
references
References 36 publications
1
45
0
Order By: Relevance
“…66 As previously reported, 72 (À)-furodysinin, exhibited feeding deterrent and ichthyotoxic properties, and additionally, concentration of the compound in the dorsal horn glands of the animals, supports the proposed defensive role of the dorsal horns. 66 Chromodoris is the most examined of all nudibranch genera, with many reported studies, 8,39, although many of the species in these studies originally classied as Chromodoris have been reclassied as Doriprismatica, 75 Felimida, 73,76,79,80,85,87,90,93 Glossodoris 79,101 Goniobranchus 39,86,88,89,95,98,[102][103][104] or Hypselodoris. 74,106 Chromodoris species feed exclusively on sponges and sequester a large number of terpenoid metabolites from their prey including sesquiterpenes, 73,74,78,82,106 norditerpenes, 80 diterpenes 8,76,81,[85][86][87][88][89][90]93,95,96,98,99,…”
Section: Chromodorididaementioning
confidence: 99%
“…66 As previously reported, 72 (À)-furodysinin, exhibited feeding deterrent and ichthyotoxic properties, and additionally, concentration of the compound in the dorsal horn glands of the animals, supports the proposed defensive role of the dorsal horns. 66 Chromodoris is the most examined of all nudibranch genera, with many reported studies, 8,39, although many of the species in these studies originally classied as Chromodoris have been reclassied as Doriprismatica, 75 Felimida, 73,76,79,80,85,87,90,93 Glossodoris 79,101 Goniobranchus 39,86,88,89,95,98,[102][103][104] or Hypselodoris. 74,106 Chromodoris species feed exclusively on sponges and sequester a large number of terpenoid metabolites from their prey including sesquiterpenes, 73,74,78,82,106 norditerpenes, 80 diterpenes 8,76,81,[85][86][87][88][89][90]93,95,96,98,99,…”
Section: Chromodorididaementioning
confidence: 99%
“…The five new diterpenes 1-5 ( Figure 1) were isolated from the Et 2 O extract of a single specimen of G. splendidus (#1106) collected at Coffs Harbour, together with aplyroseols 1-6 and 10-12 [14,15], dendrillols 1-3 [16], aplysulphurin [17], aplyviolene [18], ambliofuran [19], 12-acetoxyspongian-16-one [11] and methyl 15,17-epoxy-17-acetoxy-ent-isocopalan-16-oate [10], all of which are terpene structures previously isolated from mollusks and/or their dietary sponges. The isolated metabolites were purified by silica flash chromatography followed by NPHPLC separation.…”
Section: Diterpenes From Goniobranchus Splendidusmentioning
confidence: 99%
“…Typically, these mollusks contain terpene metabolites [1][2] that may be involved in their chemical defense [3][4][5]. Our recent studies have investigated the chemistry and anatomical location of metabolites in a range of chromodorid mollusks, including from the genera Glossodoris [6][7][8], Chromodoris [9][10][11], and Goniobranchus [8,12,13]. We found that specimens of Goniobranchus splendidus collected near Mooloolaba, South East Queensland contained "gracilin" norditerpenes with extensively rearranged carbon skeletons [12], while specimens collected at Coffs Harbor or Sydney (both New South Wales) contained rearranged norditerpenes with a tetrahydroaplysulphurin, tyrinnal or gracilane skeleton [13].…”
mentioning
confidence: 99%
“…As part of our ongoing chemoecological studies, we have reported the terpene chemistry of Chromodorid nudibranchs from various species of Glossodoris [16], Chromodoris [17], Goniobranchus [18] and Ardeadoris [19]. To the best of our knowledge, chemical analysis of Chromodorid nudibranchs of the genus Miamira has not been reported elsewhere.…”
Section: Introductionmentioning
confidence: 99%